Application of Hough Transformation Method for Value Analysis Rupiah Coins - M. Husni Rifqo; Yulia Darnita; Dwita Deslianti; Wildo Zen (Penerbit Jurnal Indonesia, 2022)
Digital image processing is one of the uses of computer technology used to solve problems regarding image processing or imagery so that it is easy to process. The process of applying image processing in this study aims to detect the value analysis of Rupiah coins by applying the Hough Transformation method, with the hough transformation method is expected to detect the nominal of coins because this method is an image transformation technique that can be used to isolate an object in the image by finding its boundaries. From research that has been conducted 10 images of coins on nominal inputs in the form of rupiah coin coins with a nominal value of 100, 200, 500, and 1000 rupiah obtained an accuracy rate of 90%. This means that there are 8 test data that get a true positive (TP) information, meaning that the data is successful, 1 false positive test data (FP) means that the data is not expected because it only gets a nominal result of the etapi coin not being parameterized in the circle of the coin and 1 test data gets a false negative (FN) description, meaning that the test result is wrong in assessing the nominal of the coin due to the image resolution factor that is too small.